Mechanistic Study on Ligand‐Controlled Cobalt‐Catalyzed Regioselectivity‐Switchable Hydroarylation of Styrenes. Issue 36 (25th July 2013) - Yang, Zhiwei; Yu, Haizhu; Fu, Yao
Abstract Density functional theory (DFT) calculations have been performed to study the mechanism of the recently reported Co‐catalyzed ligand‐controlled hydroarylation of styrenes as a means of preparing 1, 1‐ or 1, 2‐diarylalkanes. The present study corroborates the previously proposed three‐step mechanism, comprising CH activation (CH oxidative addition), styrene insertion, and reductive elimination. In the CH activation and reductive elimination steps, our calculations suggest that styrene does not coordinate to the Co center. In the insertion step, styrene is inserted into the CoH bond rather than the CoC bond. Furthermore, the rate‐ and regiodetermining step is found to be CC reductive elimination. It is significant that the regioselectivity observed experimentally has been successfully reproduced by our calculations. More importantly, in analyzing the origin of the ligand‐controlled regioselectivity, we have found that the steric effects of different ligands mainly determine the observed regioselectivity. Both the shape (i.e., "umbrella‐up" or "umbrella‐down") and bulkiness of the ligand contribute to the steric effect.